The Trend of Utilization of Dental and Oral Health Services Among Children in Iran During 2019–2021: A Cross‐Sectional Study - Somayeh Khoramian Tusi; Behrooz Pouragha; Edris Hasanpoor; Morteza Nazari (Health Science Reports)
ABSTRACT Background and Aims Oral health issues present substantial obstacles for children and teenagers globally, affecting their holistic health. With Iranian children experiencing a high prevalence of dental cavities, understanding their utilization of dental services and the influencing factors is essential. Therefore, this study examined the utilization of dental and oral health services by children aged 6 to 14 at healthcare centers in Karaj, Iran, in 2019–2021. Methods This descriptive cross‐sectional study included 361 children between 6 and 14 years old who visited healthcare centers in Karaj for dental services. The researchers developed a questionnaire to collect data. Data analysis was conducted using SPSS‐21 software, Smirnov–Kolmogorov, and Spearman's correlation test. Results Analysis of the data indicated that the utilization of dental and oral health services had significant correlations with the place of residence (p < 0.001), the father's education (p < 0.05), the number of children in the family (p < 0.005), and insurance coverage (p < 0.05). However, household income and the mother's education had no significant relationship with the utilization of dental and oral health services for the children in healthcare centers (p > 0.05). Conclusions Advocate for policies promoting oral health equity, addressing dental service access disparities, and supporting preventive measures in underserved communities, provision of insurance coverage for dental services can lead to improving the oral health of children.